Warnafusi: A Colour-Based Board Game Framework for Interdisciplinary Education - Ghifari, Fadhil Muhammad; Pertiwi , Ratih (Indo-MathEdu Intellectuals Journal, 2025)
Warnafusi is designed as a creative board game to encourage students to learn across subjects through the combination of colors and the selection of different scenarios. This article reviews how the game has evolved, how it works, and what it can offer to students. The game is designed for 2–4 players who can enjoy the game in 30–60 minutes. By combining gamification, cognitive learning, and social interaction, Warnafusi serves as a versatile tool that enhances interest and memory retention of facts in subjects such as science, math, and history, both in and out of school. Developing Warnafusi followed a qualitative descriptive and iterative process, focusing on the design and analysis of concepts. The prototype was reviewed by a panel of subject matter experts, including educators from diverse disciplines, game designers, and pedagogical consultants. Data were collected through classroom observation, focus group discussions with students, and teacher interviews. The analysis results show that Warnafusi introduces a style that is useful for integrating concepts from color theory, strategy, and social elements into one course. Because its challenge cards are customizable, this course is suitable for learning situations in schools and casual environments. By using color combinations as a method, this course inventively enhances gamification in education by improving a person's mental and social abilities. Warnafusi exemplifies the potential of board games to enrich the learning experience